Relationship between genu varum and sprint and jump performance in elite youth soccer players - Henze, A. S.; Wiedemann, P.; Bizjak, D. A.; Matits, L.; Kirsten, J.; Schulz, S. V. W. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Genu varum has been shown to be particularly prevalent in soccer players and to increase over time. Several causes have been suggested for genu varum in soccer, including muscular asymmetry and imbalanced overloading of the growth plates. Studies have also shown that this process already begins in childhood and adolescence. The development and increase of genu varum lead to biomechanical changes, increases the risk of osteoarthritis and causes tension shifts within the ligaments. This exploratory study aims to provide insight into the relationship between genu varum and athletic performance in elite youth soccer players. METHODS: In this study, 247 healthy male soccer players in the Under-12 to Under-18 squads (age 14.64 ± 2.13 years (mean ± standard deviation); body weight: 56.82 ± 14.42 kg, standing body height: 168.19 ± 13.2 cm, years of playing soccer: 9.07 ± 2.76 years, skeletal muscle mass: 28.53 ±7.94 kg) from two German elite youth academies were investigated in August 2023. Performance tests included the 30m linear sprint, the counter movement jump (CMJ), and the heading jump. The intercondylar distance (ICD) was measured using a digital caliper in cm. A linear regression was performed between the ICD and the performance parameters sprint speed (30m linear sprint) and CMJ or heading jump height. An alpha level of .05 (2-tailed) was considered significant. RESULTS: The overall mean ICD was 1.92 ± 1.8 cm. Regression analysis revealed significant relationships for sprint speed (beta = -0.46, p * .001), CMJ jump height (beta = 0.53, p * .001), and for heading jump height (beta = 0.41, p * .001). Significant relationships were also found for sprint speed (beta = -0.14, p * .001), CMJ jump height (beta = 0.18, p * .001), and for heading jump height (beta = 0.09, p * .04), when the model was adjusted for the athlete`s skeletal muscle mass. CONCLUSION: Our study provides evidence that genu varum is associated with an increase in sprint and jump performance in elite male youth soccer players. Future research is warranted in female athletes and in other team sports with similar physical demands.